BERTRAND CURVES IN GALILEAN SPACE AND THEIR CHARACTERIZATIONS - Ogrenmis, Alper Osman; Oztekin, Handan; Ergut, Mahmut (Univ Kragujevac, Fac Science, 2009)
In this paper, we introduce the notion of Bertrand and Mannheim curve in Galilean space G(3) and give characterizations of such curves.